Nominal Word Formations in Toba Batak Language: A Study of Generative Morphology - Ambarita, E; Sibarani, R; Widayati, D; Setia, E (KnE Social Sciences, 2018)
The objective of this paper is to explore nominal word formations in Toba Batak language. The theory applied in this study is generative morphology proposed by Halle (1973). The basic principle in generative morphology is that the process of word formations can generate actual words and potential words. According to generative morphology the mechanism of word formations will be postulated in list of morphemes, word formation rules, filter, and dictionary. The method of this study is qualitative descriptive; it is a method of study which describes language phenomena naturally without any exception. The results show that nominal word formations in Toba Batak language are distinguished in 3 main ways, they are: [1] by attaching affixations, [2] by inserting premodifier ni between adjectival bases and nominal bases, and [3] by moving the stress of free adjectival bases from the first syllable to the second syllable. There are 14 affixations that can form nouns in Toba Batak language, they are: (i) six prefixes (par-, na-, sa-, sanha-, hina-, ha-), (ii) two infixes (-ar-, -al-), (iii) one suffix (-na), (iv) four multiple affixations (ha-…-on, pa-…-an, pa-…-on, par-…-an), and (v) double affixations (par-in-). Nominal word formations derive from various free word bases, such as, free adjectival bases, free verbal bases, free nominal bases, free numeric bases, and free adverbial bases. The results of these affixations can be inflectional or derivational. Some complex words have to be put into filter to be processed morphophonologically before they are put into dictionary. Keywords: nominal word formations, affixations, generative morphology, inflectional, derivational